2005
DOI: 10.1002/neu.20103
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine mechanism for tolerance to cerebral ischemia-reperfusion injury in male rats

Abstract: Testosterone has been shown to exacerbate cerebral ischemia-reperfusion injury, which suggests that the well-known stress-induced testosterone reduction could be a protective response. We hypothesized that stress-induced testosterone reduction contributes to ischemia tolerance in cerebral ischemia-reperfusion injury in male rats. In intact male rats, stress was induced by brief anesthesia at 6 h before transient middle cerebral artery occlusion (MCAO). Testosterone levels were significantly decreased 6 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
(48 reference statements)
1
28
1
1
Order By: Relevance
“…Recent studies also demonstrate gender differences in both basal and inducible levels of various chaperones (41)(42)(43)(44) and that such gender-specific differences can be modulated by sex steroids (45,46). For example, estradiol increases chaperone expression in brain tissue (47), whereas testosterone inhibits the up-regulation of Hsp70 and Hsp90 in brain tissue following ischemia/reperfusion in rats (48). It should be noted that the neuroprotective effects of BAG1 on stroke were observed in male mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also demonstrate gender differences in both basal and inducible levels of various chaperones (41)(42)(43)(44) and that such gender-specific differences can be modulated by sex steroids (45,46). For example, estradiol increases chaperone expression in brain tissue (47), whereas testosterone inhibits the up-regulation of Hsp70 and Hsp90 in brain tissue following ischemia/reperfusion in rats (48). It should be noted that the neuroprotective effects of BAG1 on stroke were observed in male mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in the conformational maturation of signal transduction molecules (for example, nuclear hormone receptors and kinases) and in the cellular stress response [18] . The finding that HSP90 is induced in response to diverse apoptotic stimuli, such as UV, sodium arsenite and cerebral ischemia, has supported its involvement in cell survival [35][36][37] . Recently, it was reported that HSP90 could form a cytosolic complex with Apaf-1 and inhibit cytochrome c-mediated oligomerization of Apaf-1 and the activation of procaspase-9 [20] .…”
Section: +mentioning
confidence: 95%
“…Since testosterone can be aromatized to estrogen (Azcoitia et al, 2001), we hypothesized that endogenous testosterone would increase estrogen-mediated protection. However, previous work has shown that endogenous or exogenous testosterone increases excitotoxicity and lesion volume in a MCAO rodent model of ischemia (Yang et al, 2002(Yang et al, , 2005. Thus we evaluated the effect of endogenous, testicularderived testosterone on estrogen-mediated protection and outcome after SCI.…”
Section: Estrogen Endogenous Androgens and Apoptosismentioning
confidence: 97%